Long-term results after laparoscopic sleeve gastrectomy - Juodeikis, Žygimantas; Brimas, Edvardas; Straukas, Jordanas; Brimas, Gintautas (Lietuvos chirurgija, 2015)
ObjectiveThe aim of the study was to review long-term results in the morbidly of obese patients undergoing laparoscopic sleeve gastrectomy.Materials and methodsSeveral databases were searched, including Medline, Current Contents and Cochrane Library. All sleeve gastrectomy studies published until 2015 with long-term results (5 years or longer) were reviewed.ResultsTwenty studies, presenting 5-year or longer results after sleeve gastrectomy, were included in our analysis. A total of 4354 patients after laparoscopic sleeve gastrectomy were included in the selected studies, 1536 of whom were followed for at least 5 years. Their mean age was 37.9 years. Their mean preoperative body mass index was 46.3 kg/m2. The mean percentage of excess weight loss was 59.9 %, 58.5 %, 56.6 % and 56.4 % at 5, 6, 7 and 8 years, respectively. The overall complication rate was 6.47 %, and the 30-day mortality rate was 0.19 %. There was a remission or improvement of diabetes observed in 71.4 %, arterial hypertension in 64.4 %, dyslipidemia in 50.1 %, obstructive sleep apnea in 86.9 %, gastroesophageal reflux disease in 41.8 % and degenerative joint diseases in 83.9 % of the patients 5 years after sleeve gastrectomy. The mean BAROS scale score five years after laparoscopic sleeve gastrectomy was 6, which is equivalent to a very good result.ConclusionsOur study suggests that laparoscopic sleeve gastrectomy is a safe and effective bariatric surgery modality resulting in the good quality of life and a significant resolution of obesity-related comorbidities. Moreover, the excess weight loss is stableafter 5 years.
Keywords: obesity; bariatric surgery; sleeve gastrectomy